Ex-Offenders Employability Barriers and Practical Training Framework - Keshminder, Singh Jit Singh; Chuah, Soo-Cheng; Shahrom, Melissa; Ibrahim, Muhammad Azman; Mohamed, Siti Mahirah (Journal of Entrepreneurship, Business and Economics; Vol 10 No 2S1 (2022): Theme: Promoting Financial and Household Resilience, 2022)
With the marginalised group gaining greater attention for employment, this paper explores the barriers faced by ex-offenders during the hiring process. This study uses a qualitative approach via face-to-face semi-structured. Twenty-one cases were selected from the Malaysian bakery businesses since it actively hires ex-offenders. Findings demonstrate that job barriers faced by ex-offenders generally consisted of their self-efficacy belief, attitude, job-related skills, and self-appearance, which were fairly within their control to manage. Meanwhile, the type of offence and gender discrimination were two other barriers identified; however, these obstacles were beyond their control. This study is the first to propose a training framework to help relevant authorities assist the ex-offenders in reducing the employment barriers and justifying the training performance as a testimonial in convincing potential employers of their credibility. Research paper Keywords: Ex-offenders; employability barriers; job barriers; training framework; prison training; marginalised individuals Reference to this paper should be made as follows: Keshminder, S. J. S., Chuah, S. C., Shahrom, M., Ibrahim, M. A. & Mohamed, S. M. (2022). Ex-Offenders Employability Barriers and Practical Training Framework. Journal of Entrepreneurship, Business and Economics , 10 (2S1), 53–78.